IMPLEMENTASI KURIKULUM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (Upaya Mewujudkan Budaya Religius di Sekolah) - Afni Ma'rufah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2020)
The implementation of Islamic education curriculum has been less than optimal in public schools. This results in a moral decline in the younger generation. Answering this problem, religious culture sought to be realized through the implementation of the Islamic religious education curriculum. This study uses a qualitative approach. Data is collected through observation, interviews and documentation. The validity of the data is measured by extension of observation, perseverance of observation, triangulation, and checking. The results of the study show the religious culture in the Integrated Muhammadiyah Elementary School and the Maarif Ponorogo Elementary School, namely the Dhuha prayer, Smile, Salaam, Greetings, shaking hands, tolerance, Dhuhr prayer, tadarus Al-Qur'an, istighosah and do'a together. The implementation of the Islamic religious education curriculum in realizing religious culture at the Integrated Muhammadiyah Elementary School and the Maarif Ponorogo Elementary School is through the process of teaching and learning activities in the classroom and second through extracurricular activities.